ANALISIS DAYA SIMPAN PRODUK SUSU PASTEURISASI BERDASARKAN KUALITAS BAHAN BAKU MUTU SUSU - Haris Budiyono (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2009)
Pasteurised milk has a relatively short shelf life. In the USA it is generally expected to remain drinkable for 16 - 18 days or even longer. In European countries the expected shelf life is 10 to 14 days. In some countries, including in Indonesia, the expected shelf life is only 3 to 5 days, or even less. Fluid milk processors use ultrapasteurization to achieve 60 to 90 days of extended shelf life to allow more efficient marketing and distribution ofproduct, but some consumers do not like the heatinduced off-flavors associated with high heat treatments and would prefer HTST milk. Pasteurized fluid milk shelf life is influenced by raw milk quality. According to SNI01- 3141-1998, the microbial count or total plate count (TPC) in raw milk is required to be less than 1X10 6 cfu (coloni form unit) per ml and for somatic cell count (SCC) to be less than 4 X 10s/ml. Most milk produced by dairy farmers in Indonesia has much greater counts than these requirements. Meanwhile, according to SNI 01-3951-1995, TPC in pasteurized milk is required to be less than 3 X10 4 cfu per ml Most pasteurized milk manufacturers in Indonesia use ultrapasteurization to reach the level of microbial count as required and use special packaging to prevent recontamination, both also work to increase the storage life of the product. However, there is still another concern for fluid milk processors to pay much attention on milk SCC. Although using raw milk that has a low bacterial count, and in the absence of microbial growth in pasteurized milk, enzymes associated with high SCC will cause protein and fat degradation during refrigerated storage, and produce off-flavors.